Athena X-ray Integral Field Unit on-board Event Processor: Analysis of performance of two triggering algorithms - Cobo, Beatriz; Teresa Ceballos, Mara; Peille, Philippe; Mesnager, Jean-Michel; Wilms, Jörn; Dauser, Thomas; Kirsch, Christian; Pinsard, Frederic; Cara, Christophe; Gros, Michel; Ravera, Laurent; Bandler, Simon; et al. (2018)
In the framework of the ESA Athena mission, the X-ray Integral Field Unit (X-IFU) micro-calorimeter will provide unprecedented spatially resolved high-resolution X-ray spectroscopy. For this purpose, the on-board Event Processor (EP) must initially trigger the current pulses induced by the X-ray photons hitting the detector to proceed with a reconstruction which provides the arrival time, spatial location and energy of each event. The current event triggering design is implemented in two stages: one initial trigger of the low-pass filtered derivative of the raw data to extract records containing pulses and a second stage performing a fine detection to look for all the pulses in the record. In order to establish the current baseline detection technique of the EP in the X-IFU instrument, an assessment of the capabilities of different triggering algorithms is required, both in terms of performance (detection efficiency) and computational load, as processing will take place on-board. We present a comparison of two detection algorithms, the Simplest Threshold Crossing (STC) and the model-dependent Adjusted Derivative (AD). The analysis also evaluates the (possible) negative effect of different instrumental scenarios as a reduced sampling rate. The evaluations point out that the simplest algorithm STC shows worse performance than AD for the smallest pulses separations and the lowest secondary energies. Nevertheless, checking the expected number of such pulses combinations in a typical bright source observation, we conclude that it does not have impact in the science. Moreover, the savings in the computational resources and calibration needs make STC a valuable option.
Keywords: Athena; X-ray Integral Field Unit; X-ray spectroscopy; space telescopes; instrumentation; Event Processor; pulse detection; performance analysis